Assessment of Preparation of Samples Under the Field Conditions and a Portable Real‐Time RT‐PCR Assay for the Rapid On‐Site Detection of Newcastle Disease Virus. Issue 2 (11th September 2014) - Liu, L.; Benyeda, Z.; Zohari, S.; Yacoub, A.; Isaksson, M.; Leijon, M.; LeBlanc, N.; Benyeda, J.; Belák, S.
Summary: Newcastle disease virus (NDV), also known as virulent forms of avian paramyxovirus serotype 1 (AMPV‐1), is the causative agent of Newcastle disease affecting many species of birds and causing heavy losses to the poultry industry worldwide. Early, rapid and sensitive detection of the viruses or the viral nucleic acids is very important for disease diagnosis and control. This study aimed to evaluate sample preparation under field conditions and the application of a real‐time RT‐PCR method in the portable T‐COR4 platform for the rapid, on‐site detection of NDV on a farm. In the laboratory setting, the portable real‐time RT‐PCR assay had a similar performance compared with that obtained with a larger, stationary Rotor Gene real‐time thermocycler. In the field conditions, viral nucleic acids were manually extracted just outside of animal units with minimal equipment and real‐time RT‐PCR detection was performed with the portable thermocycler T‐COR4 placed in a nearby room. The portable assay at the farm detected viral RNA in 15 samples and reached an agreement of 83% (39/47) when the same RNA preparations were tested in the Rotor Gene thermocycler under the laboratory setting. The results demonstrated the feasibility of performing field detection but also the need to improve and further simplify sample preparation procedures.